Paradigm Shift in Practice: The Role of Pharmacists in COVID-19 Management - Saghir, Samira; Hashmi, Furqan K; Khadka, Sitaram; Rizvi, Madiha (Europasian Journal of Medical Sciences, 2020)
The continuously escalating burden of COVID-19 pandemic is challenging the health care systems around the world. The healthcare professionals of different specialties throughout the globe are working day and night for its proper mitigation. Pharmacists are healthcare professionals who are working on the frontline for the management of COVID-19 in different settings. In this review, we highlight the potential roles pharmacists can play for effective management of COVID-19. The collaborative effort of all professionals, including healthcare and other stakeholders is necessary for the appropriate management of such pandemic. Pharmacists, having expertise in clinical as well as administrative aspects, can play a pivotal role in extended health services (EHS) from prevention to eradication of COVID-19. Firm determination, inter- and intra- professional collaboration, and legislative support are mandatory for the rational practice of professionalism in such disasters.